Paediatric bacteraemias in tropical Australia. (15th October 2014) - Er, Jeremy; Wallis, Peter; Maloney, Samuel; Norton, Robert
<x xml:space="preserve">Abstract</x> Aim Bacteraemias in children are an important cause of morbidity and mortality. Knowledge of local epidemiology and trends is important to inform practitioners of likely pathogens in the sick child. This study aimed to determine trends over time in pathogenic organisms causing paediatric bacteraemia in North Queensland and to audit a hospital's blood culture results with respect to contamination rate. Methods This was a retrospective review of 8385 blood cultures collected from children attending a tertiary centre in North Queensland over a 10‐year period (2001–2010). Results There were 696 positive blood cultures (8.3%) with 70 different bacterial species detected. Gram‐positive and Gram‐negative bacteria accounted for 48.6% and 51.4% of isolates, respectively. Overall, bacteraemia accounted for 4.7 per 1000 admissions. The rate of contamination was 60.6% among positive blood cultures and 5.0% for all blood cultures sampled. These results were compared with previous published reports. Notable differences were seen in the frequencies of Salmonella and group A Streptococcus bacteraemias in North Queensland when compared with other reports. There was also a decline in vaccine‐preventable infections such as S. pneumoniae and an increasing trend of community‐acquired MRSA bacteraemia. Conclusion This study has demonstrated the unique profile of causative pathogens of paediatric bacteraemias in tropical Australia. In light of the increasing prevalence of MRSA, empiric treatment for sepsis for children in this region needs to be reconsidered.